The Influence of Corporate Image and Service Quality on Customer Loyalty through Customer Satisfaction at PNM Ambon Branch - Devan Simatauw; Eduardus Suharto (International Journal of Scientific Multidisciplinary Research, 2024)
This research is used to analyze the influence of corporate image on customer loyalty, influence of service quality on customer loyalty, influence of corporate image on customer satisfaction, influence of service quality on customer satisfaction, influence of customer satisfaction on customer loyalty, influence of corporate image on customer loyalty through customer satisfaction, and influence of service quality on customer loyalty through customer satisfaction. This research uses a quantitative method, through questionnaires distributed to 88 respondents measured on a Likert scale processed using SmartPLS. The results of this study are that the company image does not have a positive and significant effect on customer loyalty, service quality does not have a positive and significant effect on customer loyalty, the company image has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty, the company image on customer loyalty through customer satisfaction has a positive and significant effect, service quality on customer loyalty through customer satisfaction has a positive and significant effect